PRAKTIK SUPPLY CHAIN MANAGEMENT TERHADAP DAYA SAING UKM MAKANAN RINGAN KOTA MAKASSAR DI ERA COVID-19 - Aidah Aabidah Hasyim; Mahyuddin Mahyuddin; Pipi Diansari (Universitas Galuh, 2022)
Since the Covid-19 pandemic hit Indonesia, the challenges of small and medium enterprises (SMEs) are getting tougher because they not only have to be highly competitive, but how to makethe small and medium enterprises (SMEs) survive in the midst of a pandemic and don't let them close. Therefore, small and medium enterprises (SMEs) need to create a competitive advantage that is different from its competitors. One of the efforts to achieve this is by optimizing the coordination of the implementation of SCM practices effectively in terms of strategic supplier partnerships, customer relationships and information sharing so that they can survive in the competition and even lead in a pandemic crisis. This study aims to analyze strategic supplier partnerships, customer relationships, information sharing and postponement of the competitiveness of small and medium enterprises (SMEs) in Makassar City in the Covid-19 pandemic era. This study used Structural Equation Modeling (SEM) data analysis with SmartPLS software. The results of this study indicates that strategic supplier partnership has no effect on the competitiveness of Snack of small and medium enterprises (SMEs) in Makassar City while customer relationships and information sharing have an influence on the competitiveness of Snacks of small and medium enterprises (SMEs) in Makassar City in the Covid-19 era.